PENGARUH KUALITAS PELAYANAN ADMINISTRASI TERHADAP KEPUAASN LAYANAN PESERTA PADA PT TASPEN CABANG MANADO - VAN GOBEL, MUZDALIFA; OGOTAN, MARTHA; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2019)
This research aims to determine if there is any influence on the quality of administrationservices to the satisfaction of participants in the service of PT. TASPEN Manado Branch and whatindicators most affect the quality of the service. Where the administrative service quality variables aremeasured through four indicators of Zeithaml's theory of existence, responsiveness, reliability, assuranceand certainty, and empathy. This research uses a descriptive quantitative method. The sample in this studywas 36 respondents. Data collection techniques used in this research with poll/questionnaire methods andinterviews.The results showed that the quality of administration service has a significant positive effect on thesatisfaction of participants in PT TASPEN Manado branch. Which means variable quality ofadministration services is a factor that determines the satisfaction of service participants. The better thelevel of quality of administration service will be better/higher also the level of customer satisfaction in theoffice of PT TASPEN Manado Branch and the indicator that most influences the quality ofadministration services is the indicator of reliability and empathy where both have the total valuecorrelation/r count the most hight than other indicators.Keywords : Quality of service Administration, satisfaction services